(untitled) - Hart, Harolt (Boston, 1959)
Designed specifically for the one-semester short course in organic chemistry, this market leader appeals to a range of non-chemistry science majors through its emphasis on practical, real-life applications of chemistry, coverage of basic concepts, and engaging visual style.
Keywords: Chemistry, organic